English Food, 1934: Irving Davis and the International Wine and Food Society - Jaine, Tom (Petits Propos Culinaires, 2013)
The article reprints the speech by Irving Davis at the first annual conference of the the International Wine and Food Society held in Brighton in 1934 in which he surveyed the state of English cooking, innkeeping and restaurants at the time.